ON THE PREUNIVERSITY PREPARATION - Hurtado Mondoñedo, Luis (2014)
This editorial part points out some of the reasons why we have to be worried about the fact that a growing number of private schools are blindly adopting pre-university preparation models. Some background on pre-university preparation models are put forward, their changes in the last few years, their influence on the school environment, and their possible modifications in the next few years.